Left vs. right radial approach for coronary catheterization: Relation to age and severe aortic stenosis - Will, Maximilian; Weiss, Thomas W.; Weber, Michael; Kwok, Chun Shing; Borovac, Josip A.; Lamm, Gudrun; Unterdechler, Markus; Aufhauser, Simone; Nolan, Jim; Mascherbauer, Julia; Schwarz, Konstantin (Frontiers in Cardiovascular Medicine, 2022)
Background Old age and the presence of aortic stenosis are associated with the unfolding of the intrathoracic aorta. This may result in increased difficulties navigating catheters from the right compared to the left radial approach. Objective To investigate whether increasing age or presence of severe aortic stenosis was associated with increased catheterization success rates from left (LRA) compared to right radial artery approach (RRA). Methods We compared coronary angiography success rates of RRA and LRA according to different age groups and in a subgroup of patients with severe aortic stenosis. Results A total of 21,259 coronary angiographies were evaluated. With increasing age, the first pass success rate from either radial access decreased significantly (p < 0.001). In patients aged <85 years, there was no difference between LRA and RRA. However, in patients aged ≥85 years, LRA was associated with significantly higher success rates compared to RRA (90.1 vs. 82.8%, p = 0.003). Patients aged ≥85 years received less contrast agent and had shorter fluoroscopy time when LRA was used [86.6 ± 41.1 vs. 99.6 ± 48.7 ml (p < 0.001) and 4.5 ± 4.1 min vs. 6.2 ± 5.7 min (p < 0.001), mean (±SD)]. In patients with severe aortic stenosis (n = 589) better first pass success rates were observed via LRA compared to the RRA route (91.9 vs. 85.1%, p = 0.037). Conclusion LRA, compared to RRA, is associated with a higher first-pass catheter success rate for coronary artery angiography in patients aged ≥85 years and those with severe aortic stenosis.